Changes in Microbial Community Diversity and the Formation Mechanism of Flavor Metabolites in Industrial-Scale Spontaneous Fermentation of Cabernet Sauvignon Wines - Chunyan Bai; Boyuan Fan; Jinmei Hao; Yuan Yao; Shiming Ran; Hua Wang; Hua Li; Ruteng Wei (Foods)
The key flavor compound formation pathways resulting from indigenous microorganisms during the spontaneous fermentation of wine have not been thoroughly described. In this study, high-throughput metagenomic sequencing and untargeted metabolomics were utilized to investigate the evolution of microbial and metabolite profiles during spontaneous fermentation in industrial-scale wine production and to elucidate the formation mechanisms of key flavor compounds. Metabolome analysis showed that the total amount of esters, fatty acids, organic acids, aldehydes, terpenes, flavonoids, and non-flavonoids increased gradually during fermentation. Enrichment analysis indicated that metabolic pathways related to the synthesis, decomposition, transformation, and utilization of sugars, amino acids, and fatty acids were involved in the formation of key flavor compounds in wine. Metagenomic analysis revealed that Saccharomyces, Hanseniaspora, Zygosaccharomyces, Wickerhamiella, Lactobacillus, and Fructobacillus were the dominant taxa during spontaneous fermentation. They were significantly positively correlated with organic acids, fatty acids, esters, phenols, aldehydes, terpenes, and phenols. In conclusion, this research provides new insights into the metabolic pathways of key flavor compounds formed by indigenous microorganisms during wine fermentation.